Silica powder
Patent Information
- Application Number
- JP2024064120
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-04-11
- Publication Date
- 2025-03-07
AI Technical Summary
【0010】 本発明によれば、樹脂に配合したときの低誘電正接および充填性に優れたシリカ粉末が提供される。
Smart Images

Figure 2025031500000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a silica powder. [Background technology]
[0002] In recent years, with the increase in the amount of information and communication in the field of communication, the use of high frequency bands in electronic devices and communication devices is spreading. High frequency bands have characteristics such as wide bandwidth, straightness, and transparency. 9 The GHz band, which is above 100 GHz, is widely used.
[0003] The use of high frequencies has led to problems such as increased transmission loss of circuit signals. Transmission loss can be broadly divided into conductor loss caused by the skin effect of wiring, and dielectric loss caused by the characteristics of the dielectric material of the insulators that make up electrical and electronic components such as circuit boards. Dielectric loss is proportional to the first power of frequency, the half power of the dielectric constant of the insulator, and the first power of the dielectric dissipation factor, so materials used in high frequency devices are required to have both low dielectric constant and dielectric dissipation factor.
[0004] Silica (SiO2) has a low dielectric constant (3.7) and a quality factor index Qf (the inverse of the dielectric tangent multiplied by the measurement frequency) of approximately 120,000, making it a promising filler material with low dielectric constant and dielectric tangent. However, the surfaces of silica particles contain a large amount of adsorbed water and polar functional groups such as silanol groups, and in particular there is a problem in that the dielectric loss tangent is worse than the properties of the sintered substrate.
[0005] In response to this, Non-Patent Document 1 discusses a method of surface treatment with a silane coupling agent as a method for reducing adsorbed water and polar functional groups on the surface of filler particles. However, the dielectric tangent is hardly reduced at 1 to 10 MHz, and the effect is insufficient, and the effect in the GHz band is not clearly stated. [Prior art documents] [Non-patent literature]
[0006] [Non-Patent Document 1] IEEE Transactions on Dielectrics and Electrical Insulation Vol. 17, No. 6(2010) Summary of the Invention [Problem to be solved by the invention]
[0007] However, as a result of investigations by the present inventors, it was found that the silica powder described in Non-Patent Document 1 above still has room for improvement in terms of low dielectric tangent and filling property when blended with a resin. [Means for solving the problem]
[0008] As a result of further investigation, the inventors of the present invention found that, in addition to the predetermined "water content measured by the Karl Fischer method," the silica powder has a "BET specific surface area" and a "particle diameter D at 90% cumulative volume measured by a wet laser method." 90 The inventors have discovered that by appropriately adjusting the particle size characteristics such as "particle diameter" and "capacity", it is possible to lower the dielectric tangent when the powder is blended with a resin while improving the fillability into the resin, and have thus completed the present invention.
[0009] According to one aspect of the present invention, there is provided a silica powder comprising: 1. The dielectric loss tangent of a resin sheet sample at 40 GHz measured according to the following procedure is 2.0×10 -3 A silica powder having the following structure: The amount of moisture generated by the time the temperature reaches 200℃ is 500ppm or less, as measured by the Karl Fischer method. The specific surface area measured by the BET single point method using nitrogen gas adsorption is 0.2 m 2 / g or more 5.4m 2 / g or less, and The particle size at the point where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 90% is defined as D 90 Then, D 90 is 3.0 μm or more and 75 μm or less, Silica powder. (procedure) The silica powder is mixed with polyethylene powder so that the filling amount is 40 volume %, and the resin sheet sample is molded using the obtained mixed powder.The dielectric loss tangent at 40 GHz is measured using the obtained resin sheet sample by a resonance method. 2. The silica powder according to 1., A silica powder having a most frequent diameter of 2.5 μm or more and 40 μm or less in particle size frequency distribution measured by a wet laser diffraction scattering method. 3. The silica powder according to 1. or 2., A silica powder having a maximum peak frequency of 10% or less in a particle size frequency distribution measured by a wet laser diffraction scattering method. 4. A silica powder according to any one of 1. to 3., The most frequent diameter in the particle size frequency distribution measured by the wet laser diffraction scattering method is Dm (μm), and the specific surface area is S (m 2 / g), Dm / S is 0.6 or more. 5. A silica powder according to any one of 1. to 4., A silica powder in which the frequency of particles having a particle size of 15.7 μm or more in the particle size frequency distribution measured by a wet laser diffraction scattering method is 50% or less. 6. The silica powder according to any one of 1. to 5., A silica powder in which the frequency of particles with a particle size of less than 0.5 μm in the particle size frequency distribution measured by a wet laser diffraction scattering method is 15% or less. 7. The silica powder according to any one of 1. to 6., The particle diameters at the points where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 10%, 50%, and 100% are defined as D 10 , D 50 , D 90 Then, (D 90 -D 10 ) / D 50 The silica powder, 8. The silica powder according to any one of 1. to 7., A silica powder having an average sphericity of 0.85 or more. 9. The silica powder according to any one of 1. to 8., Silica powder having an amorphous rate of 95.0% or more. 10. The silica powder according to any one of 1. to 9., Silica powder containing uranium and thorium elements at levels of 20 ppb or less. Effect of the Invention
[0010] According to the present invention, there is provided a silica powder which has a low dielectric tangent and excellent filling properties when blended with a resin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The silica powder of this embodiment will be outlined below.
[0012] The silica powder of this embodiment is The amount of moisture generated by the time the temperature reaches 200℃ is 500ppm or less, as measured by the Karl Fischer method. The specific surface area measured by the BET single point method using nitrogen gas adsorption is 0.2 m 2 / g or more 5.4m 2 / g or less, and The particle size at the point where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 90% is defined as D 90 Then, D 90 is 3.0 μm or more and 75 μm or less.
[0013] According to the findings of the present inventors, in silica powder, the "water content measured by the Karl Fischer method" is determined, along with the "BET specific surface area" and the "particle diameter D at 90% cumulative volume measured by the wet laser method." 90 It was found that by appropriately adjusting the particle size characteristics such as ", it is possible to reduce the dielectric tangent when blended with resin and improve the filling ability into resin. Here, by blending ultrafine powder, the filling state of silica powder in the resin can be improved, but the specific surface area of ultrafine powder is large, so the dielectric tangent of the resin sheet may increase. As a result of intensive research by the inventors, it was found that by using ultrafine powder that has been sufficiently heat-treated, it is possible to achieve both filling property and low dielectric tangent. In addition, the resin composition containing the silica powder having the appropriate particle size characteristics as described above has a high filling ability into narrow gaps during molding, and therefore the silica powder can be highly filled. This makes it possible to reduce the dielectric tangent of a thin molded body of the resin composition.
[0014] The silica powder of this embodiment has a dielectric loss tangent of 2.0×10 at 40 GHz of the resin sheet measured by the following procedure. -3 It satisfies the following: The upper limit of the dielectric tangent at 40 GHz is 2.0×10 -3 Less than or equal to 1.9×10 -3 Less than or equal to 1.5×10 -3 Less than 0.5×10, more preferably -3 The following is the result. The lower limit of the dielectric loss tangent at 40 GHz is not particularly limited, but is, for example, 1.0×10 -6 It may be more than that.
[0015] (Measuring procedure for dielectric tangent) Silica powder is mixed with polyethylene powder so that the filling amount is 40 volume %, and the resulting mixed powder is used to mold a resin sheet sample. The dielectric loss tangent at 40 GHz is measured using the resulting resin sheet sample by the resonance method.
[0016] The silica powder of the present embodiment can be suitably used as a filler to be mixed into resin materials such as resins or resin compositions. The resin materials can be used for various purposes, and can be used, for example, as high-frequency resin materials.
[0017] The composition of the silica powder of this embodiment will be described in detail below.
[0018] <Silica powder> The silica powder may be any powder containing silica (SiO2) as a main component. The term "main component" means that the silica powder contains, for example, 50% or more, preferably 80% or more, and more preferably 90% or more, of silica (SiO2) in terms of mass, based on the total amount of the silica powder. The silica powder preferably has a high purity, but the presence of impurities that are inevitably mixed in from the raw materials or during the production process is acceptable.
[0019] The silica powder may be either or both of amorphous and crystalline. The amorphous rate of the silica powder is, for example, 95.0% or more, preferably 97.0% or more, and more preferably 99.0% or more.
[0020] The amorphous ratio of the silica powder is measured by X-ray diffraction analysis using a powder X-ray diffractometer (for example, Model MiniFlex manufactured by RIGAKU Corporation) in the 2θ range of 26° to 27.5° with CuKα radiation, and is measured from the intensity ratio of specific diffraction peaks. In the case of siliceous powders, crystalline silica has a main peak at 26.7°, but amorphous silica has no peak. When amorphous silica and crystalline silica are mixed, the height of the peak at 26.7° depends on the proportion of crystalline silica. Then, the crystalline silica mixing ratio (X-ray diffraction intensity of sample / X-ray diffraction intensity of crystalline silica) can be calculated from the ratio of the X-ray intensity of the sample to the X-ray intensity of the crystalline silica standard sample, and the amorphous ratio (%) can be calculated from the formula, amorphous ratio (%) = (1 - crystalline silica mixing ratio) x 100.
[0021] The shape of the silica powder may be any of spherical, crushed, needle-like, flake-like, etc., but the spherical shape is preferred.
[0022] The average circularity of the silica powder is, for example, 0.85 or more, preferably 0.90 or more, and more preferably 0.95 or more, which can suppress an increase in viscosity and a decrease in flowability when the silica powder is mixed with a resin.
[0023] The average sphericity of the silica powder is measured as follows. Particle images taken with a stereomicroscope (for example, Nikon Model "SMZ-10"), a scanning electron microscope, or the like, are input into an image analyzer (for example, Nippon Avionics Co., Ltd.). The projected area (A) and perimeter (PM) of the particle are measured from the photograph. If the area of a perfect circle corresponding to the perimeter (PM) is (B), the circularity of the particle can be expressed as A / B. If we assume a perfect circle with the same perimeter as the perimeter (PM) of the sample particle, PM=2πr, B=πr 2 Therefore, B = π × (PM / 2π) 2 The sphericity of each particle is given by: Sphericity = A / B = A × 4π / (PM) 2 It can be calculated as follows: The circularity of 200 randomly selected particles thus obtained was determined, and the average value was taken as the average sphericity.
[0024] The upper limit of the specific surface area of silica powder is 5.4 m 2 / g or less, preferably 5.0m 2 / g or less, more preferably 4.0m 2 / g or less. This makes it possible to reduce the dielectric tangent when blended with a resin. On the other hand, the lower limit of the BET specific surface area is 0.2 m 2 / g or more, preferably 0.3m 2 / g or more, more preferably 0.4m 2 This makes it possible to suppress a decrease in fluidity when blended with a resin.
[0025] The specific surface area of the silica powder can be measured by the BET one-point method using nitrogen gas adsorption. Specifically, a specific surface area measuring device (manufactured by Anton Paar, device name: NOVA 800 BET) is used, nitrogen gas is transported as the adsorption gas by a vacuum pump, and 0.1 to 5.0 g of the sample is dried and degassed at 300°C for 30 minutes before measurement.
[0026] The upper limit of the most frequent diameter in the particle diameter frequency distribution of the silica powder is, for example, 40 μm or less, preferably 30 μm or less, and more preferably 20 μm or less, which can further improve the filling property of the resin material containing the silica powder. On the other hand, the lower limit of the mode diameter is, for example, 2.5 μm or more, preferably 3.0 μm or more, and more preferably 4.0 μm or more, which can suppress an increase in viscosity of the resin material containing the silica powder.
[0027] The upper limit of the frequency of the maximum peak in the particle size frequency distribution of the silica powder is not particularly limited, but is, for example, 10% or less, preferably 9.5% or less, and more preferably 9.0% or less. On the other hand, the lower limit of the frequency of the maximum peak is, for example, 2.0% or more, preferably 3.5% or more, and more preferably 4.0% or more. The particle size frequency distribution that satisfies the upper limit of the frequency of the maximum peak has a relatively broad profile. This can improve the filling property of the resin material containing the silica powder.
[0028] The most frequent diameter in the particle size frequency distribution of the silica powder is Dm (μm), and the specific surface area of the silica powder is S (m 2 / g), and the value of the most frequent diameter / the specific surface area is defined as Dm / S. The upper limit of Dm / S in the silica powder is not particularly limited, but is, for example, not more than 50, preferably not more than 40, and more preferably not more than 30. This can further improve the filling property of the resin material containing the silica powder. On the other hand, the lower limit of the Dm / S is, for example, 0.5 or more, preferably 1.2 or more, and more preferably 1.6 or more, which can improve the filling property of the resin material containing the silica powder.
[0029] In addition, the number of peaks showing a frequency maximum within the range of 2.5 μm or more and 40 μm or less in the particle size frequency distribution of the silica powder may be one or more. When a silica powder has multiple peaks, the peak with the highest frequency is defined as the "maximum peak."
[0030] The upper limit of the frequency of particles having a particle diameter of 15.7 μm or more in the particle diameter frequency distribution of the silica powder is, for example, 50% or less, preferably 20% or less, more preferably 10% or less, and further preferably 1.0% or less, which can improve the filling property of the resin material containing the silica powder. On the other hand, the lower limit of the frequency of particles having a particle size of 15.7 μm or more is not particularly limited, but may be 0% or more, or 0.1% or more.
[0031] The upper limit of the frequency of particles having a particle diameter of less than 0.5 μm in the particle diameter frequency distribution of the silica powder is, for example, 15% or less, preferably 6.0% or less, and more preferably 1.0% or less, which can suppress an increase in viscosity of the resin material containing the silica powder. On the other hand, the lower limit of the frequency of particles having a particle size of less than 0.5 μm is not particularly limited, but may be 0% or more, or 0.1% or more.
[0032] The particle diameters at the points where the cumulative volume from the small particle side in the volume frequency particle size distribution of silica particles is 10%, 50%, and 90% are D 10 , D 50 , D 90 Let us assume that.
[0033] D 90 The upper limit of the particle size is 75 μm or less, preferably 50 μm or less, and more preferably 30 μm or less. This can further improve the filling property of the resin material containing the silica powder. On the other hand, D 90 The lower limit of the particle size is 3.0 μm or more, preferably 4.0 μm or more, and more preferably 5.0 μm or more. This makes it possible to suppress an increase in viscosity of the resin material containing the silica powder.
[0034] (D 90 -D 10 ) / D 50 is, for example, not more than 10, preferably not more than 5, and more preferably not more than 3.0. This makes it possible to suppress an increase in viscosity of the resin material containing the silica powder. On the other hand, (D 90 -D 10) / D 50 The lower limit is, for example, 0.3 or more, preferably 0.7 or more, and more preferably 1.0 or more.
[0035] The particle size frequency distribution and volume frequency particle size distribution of silica powder are values based on particle size measurement by a wet laser diffraction light scattering method, and can be measured using, for example, a particle size distribution measuring device, LS13 320 manufactured by Coulter. When measuring, water is used as a solvent, and as a pretreatment, a dispersion treatment can be performed by applying 500W output using a homogenizer for 120 seconds or more. In addition, the PIDS (Polarization Intensity Differential Scattering) concentration is adjusted to 45 to 55%. The refractive index of water is 1.33, and the refractive index of the powder is determined by considering the refractive index of the powder material. For example, the refractive index of amorphous silica is measured at 1.50.
[0036] In the silica powder, the upper limit of the amount of moisture (physically adsorbed water) generated before the temperature reaches 200° C. as measured by the Karl Fischer method is 500 ppm or less, preferably 490 ppm or less, and more preferably 480 ppm or less, which can further reduce the dielectric tangent when blended with a resin. On the other hand, the lower limit of the physically adsorbed water is not particularly limited, but may be 0 ppm or more, or 1 ppm or more.
[0037] The water content in the silica powder is measured by the Karl Fischer method. Specifically, a trace moisture measuring device (Mitsubishi Chemical Corporation, Model CA-05) was used, the powder was placed in a quartz tube in a moisture vaporization mechanism, and dehydrated argon gas was supplied as a carrier gas while heating from room temperature to 900°C with an electric heater, and the water vapor evaporated from the powder surface was guided to the moisture measurement mechanism to measure the moisture content. The moisture generated before the heating temperature of the electric heater reached 200°C was considered to be physically adsorbed water.
[0038] The upper limit of the content of uranium and thorium in the silica powder is, for example, 20 ppb or less, preferably 10 ppb or less, and more preferably 1.0 ppb or less, which can suppress the occurrence of defects in devices such as memories. On the other hand, the lower limits of the contents of the uranium and thorium elements are not particularly limited, but may be, for example, 0.1 ppb or more.
[0039] The content of uranium and thorium elements in the silica powder is measured using an inductively coupled plasma mass spectrometer (ICP-MS).
[0040] In this embodiment, for example, by appropriately selecting the raw material components of the silica powder and the manufacturing method of the silica powder, it is possible to control the above-mentioned dielectric loss tangent, specific surface area, various values obtained from the particle size frequency distribution, and various values obtained from the volume frequency particle size distribution. Among these, for example, using silica powder manufactured by a dry method, dry classification, blending heat-treated ultrafine powder, etc. are listed as elements for making the above-mentioned dielectric loss tangent, specific surface area, various values obtained from the particle size frequency distribution, and various values obtained from the volume frequency particle size distribution within the desired numerical range.
[0041] <Method of manufacturing silica powder> As an example of the manufacturing method of the present embodiment, raw material silica powder manufactured by a dry method is classified, and then blended with ultrafine powder to obtain silica powder. In addition, the classification process can be carried out by mixing or classifying appropriate amounts of silica powders having different particle size configurations. Industrially, classification using a classifier such as a sieve or a precision air classifier is desirable, and the classification operation is preferably a dry method. By dry classifying raw silica powder produced by a dry method, it is possible to suppress aggregation of the silica powder and improve handleability, etc., compared to the case where raw silica powder produced by a wet method and / or wet classification is used. The obtained silica powder is desirably stored in a moisture-proof bag.
[0042] The classified silica powder may be subjected to a heat treatment as one of the post-treatments. The heat treatment is performed in a hot air or electric furnace at a temperature of 500 to 1100°C for a predetermined time (e.g., about 1 to 52 hours) such that heating temperature (°C) × heating time (h) is 1000 to 26400 (°C·h), preferably for a predetermined time (e.g., about 2 to 35 hours) such that heating temperature (°C) × heating time (h) is 1800 to 17600 (°C·h). If the heating temperature is 500 to 1100°C, the specific surface area and average particle size do not change before and after heating, so it is desirable to carry out the classification process before heating and then adjust the specific surface area and average particle size to the desired values before carrying out the heat treatment. After the heat treatment, the silica powder is naturally cooled in the electric furnace, and then collected at 110°C to 300°C. It is further cooled to 25°C in an environment with a humidity of 40% RH or less, and stored at 15 to 25°C. It may also be collected and stored in a moisture-proof aluminum bag.
[0043] The ultrafine powder blending process is a process in which ultrafine silica powder having a smaller particle size than the classified silica powder is blended in a predetermined ratio. The particle size of the ultrafine silica powder may be, for example, 2 μm or less in terms of D50, and is preferably 0.1 μm or more and 1.5 μm or more. The blending amount of the ultrafine silica powder is preferably, for example, 5% by mass or more and 35% by mass, when the total silica powder is taken as 100% by mass. The ultrafine silica powder is preferably subjected to the above-mentioned heat treatment before blending.
[0044] The method for storing silica powder is to store it in a container with a moisture permeability of 0.1 (g / m2) under condition B of JIS Z 0208-1976 (temperature 40°C, relative humidity 90%). 2 It is preferable to store the product in a moisture-proof bag for up to 24 hours, such as a moisture-proof aluminum bag or a PET / AL / PE laminate bag.
[0045] Next, the resin composition of the present embodiment will be described. A resin composition containing the silica powder of this embodiment can be suitably used as a resin material. The resin composition contains, in addition to the silica powder of this embodiment, a resin and known resin additives.
[0046] In the resin composition, the silica powder may be used alone or may be mixed with other fillers. The resin composition may contain 10 to 99% by mass of the silica powder, or 10 to 99% by mass of a mixed inorganic powder containing the silica powder and other fillers. The content of the other fillers in the mixed inorganic powder may be, for example, 1 to 20% by mass or 3 to 15% by mass relative to 100% by mass of the silica powder. In this specification, the symbol "to" indicates that both the upper and lower limits are included, unless otherwise specified.
[0047] Examples of other fillers include silica other than the silica powder of this embodiment, alumina, titania, silicon nitride, aluminum nitride, silicon carbide, talc, calcium carbonate, and the like. The other fillers have an average particle size of about 5 to 100 μm, and there are no particular restrictions on the particle size composition and shape.
[0048] Examples of the resin include epoxy resin, silicone resin, phenol resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyamide such as polyimide, polyamideimide, polyetherimide, polyester such as polybutylene terephthalate, polyethylene terephthalate, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyethersulfone, polycarbonate, maleimide modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber-styrene) resin, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resin, etc. These may be used alone or in combination of two or more.
[0049] The resin composition can be produced, for example, by blending raw material components in a predetermined ratio using a blender or a Henschel mixer, kneading the mixture using a heated roll, a kneader, a single-screw or twin-screw extruder, or the like, cooling the mixture, and then pulverizing it.
[0050] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0051] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples. <Preparation of Silica Powder> [Examples 1 to 5] The silica powder was prepared according to the following procedure. The raw material used was commercially available silica powder A produced by a dry method. Silica powder A used as the raw material had one mode diameter peak in the range of 2.5 to 40.0 μm.
[0052] (Dry classification) First, the raw silica powder was dry classified using a precision air classifier to remove large particles. The particle size frequency distribution showed the frequency of particles with a particle size of 15.7 μm or more as shown in Table 1.
[0053] (Contains ultra-fine powder) Next, a specified amount of ultrafine silica powder with a D50 of 2 μm or less was mixed with the silica powder after dry classification. The frequency of particles with a particle size of less than 0.5 μm in the particle size frequency distribution was obtained as shown in Table 1.
[0054] (Post-treatment 1: Heat treatment) In Examples 1 and 3, the silica powder after dry classification was subjected to a heat treatment before the ultrafine powder was mixed. In the heat treatment, the silica powder was filled into an alumina crucible and heat-treated in air at 1000°C in an electric furnace for 4 hours. After the heat treatment, it was cooled to 200°C in the furnace and then cooled to room temperature in a desiccator (23°C, 10% RH), and the heat-treated silica powder was collected.
[0055] (Post-treatment 2: Heat treatment) In Examples 1 to 5, ultrafine silica powder having a D50 of 2 μm or less was subjected to a heat treatment before being mixed with the ultrafine silica powder. In the heat treatment, the silica powder was filled into an alumina crucible and heat-treated in air at 1000°C in an electric furnace for 4 hours. After the heat treatment, it was cooled to 200°C in the furnace and then cooled to room temperature in a desiccator (23°C, 10% RH), and the heat-treated ultrafine silica powder was collected.
[0056] [Comparative Example 1] Commercially available silica powder B produced by a dry method was used, and the above-mentioned (dry classification) and (post-treatment 1: heat treatment) were carried out to obtain a silica powder. Silica powder B had no mode diameter peak in the range of 2.5 to 40.0 μm, and had one mode diameter peak in the range exceeding 40.0 μm.
[0057] [Comparative Example 2] As the raw material, commercially available silica powder C produced by a dry method was used, and only the above-mentioned (dry classification) was carried out to obtain a silica powder. Silica powder C used as the raw material had no mode diameter peak in the range of 2.5 to 40.0 μm, and had one mode diameter peak in the range of less than 2.5 μm.
[0058] [Comparative Example 3] As the raw material, commercially available silica powder D produced by a dry method was used, and only the above-mentioned (dry classification) and (post-treatment 1: heat treatment) were carried out to obtain a silica powder. Silica powder D used as the raw material had no mode diameter peak in the range of 2.5 to 40.0 μm, and had one mode diameter peak in the range of less than 2.5 μm.
[0059] [Comparative Example 4] The raw material was a commercially available silica powder E produced by a dry method, and the above-mentioned (dry classification), (post-treatment 1: heat treatment), and (blending of ultrafine powder) were carried out only to obtain the above-mentioned silica powder. Silica powder E used as the raw material had one mode diameter peak in the range of 2.5 to 40.0 μm.
[0060] [Comparative Example 5] As the raw material, commercially available silica powder F produced by a dry method was used, and the above-mentioned (post-treatment 2: heat treatment) was not carried out, but only the above-mentioned (dry classification) and the above-mentioned (post-treatment 1: heat treatment) were carried out to obtain a silica powder. Silica powder F used as the raw material had one mode diameter peak in the range of 2.5 to 40.0 μm.
[0061] The silica powder obtained in each of the Examples and Comparative Examples was stored in an aluminum bag until immediately before various evaluations.
[0062] [Table 1]
[0063] The obtained silica powder was evaluated for the following items.
[0064] <Dielectric loss tangent measured by the resonance method> The silica powder was mixed with polyethylene powder (Sumitomo Seika Chemicals, Flowthen UF-20S) to a loading of 40 volume % using a vibration mixer (Resodyn) under conditions of an acceleration of 60 g and a processing time of 2 minutes. The obtained mixed powder was weighed out to a specified volume (so that the thickness was about 0.3 mm), placed in a metal frame with a diameter of 3 cm, and molded in a heat press machine (Imoto Manufacturing Co., Ltd. "IMC-1674-A type") under molding conditions of 140°C, 10 MPa, and 15 minutes to mold a resin sheet sample of 1.5 cm square and 0.3 mm thick. Note that the shape and size of the resin sheet sample do not affect the evaluation results as long as it can be mounted on the measuring device. Using the obtained resin sheet sample, a 40 GHz cavity resonator (manufactured by Samtec) was connected to a vector network analyzer (85107, manufactured by Keysight Technologies), and the 10 mm diameter hole in the resonator was set to be blocked, and the resonant frequency (f0) and unloaded Q value (Qu) were measured. The sample was rotated for each measurement, and the measurement was repeated five times in the same manner. The average of the obtained f0 and Qu was taken as the measured value. The dielectric constant was calculated from f0, and the dielectric loss tangent (tan δc) was calculated from Qu using analysis software (SAMTECH software). The measurement temperature was 20°C, and the humidity was 60% RH. The obtained tan δc was defined as the dielectric tangent of the resin sheet sample.
[0065] <Specific surface area> The specific surface area of the silica powder was measured by the BET one-point method using nitrogen gas adsorption. Specifically, a specific surface area measuring device (manufactured by Anton Paar, device name: NOVA 800 BET) was used, nitrogen gas was transported by a vacuum pump, and 0.1 to 5.0 g of sample was dried and degassed at 300° C. for 30 minutes before measurement.
[0066] <Particle size> The particle size frequency distribution and volume frequency particle size distribution of the silica powder were determined by a wet laser diffraction scattering method using a particle size distribution measuring device (LS13 320, manufactured by Coulter). Water was used as the solvent, and as a pretreatment, the powder was dispersed using a homogenizer at an output of 500 W for 120 seconds or more and measured. In addition, the PIDS (Polarization Intensity Differential Scattering) concentration was adjusted to 45 to 55% and measured. The refractive index of water was 1.33, and the refractive index of the powder was determined by considering the refractive index of the powder material. For example, the refractive index of amorphous silica was measured at 1.50. Based on the obtained particle size frequency distribution, the "mode diameter," "frequency of the maximum peak," "frequency of particle sizes less than 0.5 μm," and "frequency of particle sizes 15.7 μm or more" were calculated. Based on the obtained volume frequency particle size distribution, the particle size (D X ) was calculated.
[0067] <Average sphericity> The average sphericity of silica powder was measured by importing particle images taken with a stereomicroscope (e.g., Nikon Model "SMZ-10") or scanning electron microscope into an image analyzer (e.g., Nippon Avionics Co., Ltd.) as follows. That is, the projected area (A) and perimeter (PM) of the particle were measured from the photograph. If the area of a perfect circle corresponding to the perimeter (PM) is (B), the circularity of the particle can be expressed as A / B. Therefore, assuming a perfect circle with the same perimeter as the perimeter (PM) of the sample particle, PM=2πr and B=πr 2 Therefore, B = π × (PM / 2π) 2 The sphericity of each particle is given by: Sphericity = A / B = A × 4π / (PM) 2 The circularity of 200 randomly selected particles thus obtained was determined, and the average value was taken as the average sphericity.
[0068] <Moisture content> The water content in the silica powder was measured by the Karl Fischer method. Specifically, a trace moisture measuring device (Model CA-05, manufactured by Mitsubishi Chemical Corporation) was used. The powder was placed in a quartz tube in a moisture vaporization mechanism, and heated from room temperature to 900°C using an electric heater while dehydrated argon gas was supplied as a carrier gas. The water vapor evaporated from the powder surface was introduced into the moisture measurement mechanism to measure the moisture content. The moisture generated before the heating temperature of the electric heater reached 200°C was considered to be physically adsorbed water, the moisture generated between 200°C and 550°C was considered to be water derived from hydrogen-bonded OH groups, and the moisture generated between 550°C and 900°C was considered to be water due to dehydration condensation of isolated OH groups.
[0069] <Amorphous ratio> The amorphous ratio of the silica powder was measured from the intensity ratio of specific diffraction peaks by X-ray diffraction analysis using a powder X-ray diffractometer (manufactured by RIGAKU Corporation, product name "Model MiniFlex") in the 2θ range of 26° to 27.5° with CuKα radiation. Specifically, the crystalline silica mixing ratio (X-ray diffraction intensity of sample / X-ray diffraction intensity of crystalline silica) was calculated from the ratio of the X-ray intensity of the sample (obtained silica powder) to the X-ray intensity of the crystalline silica standard sample, and the amorphous ratio (%) was calculated from the formula: amorphous ratio (%) = (1 - crystalline silica mixing ratio) × 100.
[0070] <Uranium and thorium content> The uranium and thorium content (ppb) of the silica powder was measured using an inductively coupled plasma mass spectrometer (ICP-MS).
[0071] <Spiral flow: Evaluation of fluidity> 85.0% by mass of the silica powder obtained above, 8.04% by mass of epoxy resin (manufactured by Nippon Kayaku Co., Ltd., NC-3000P), 6.08% by mass of phenol resin (manufactured by Meiwa Kasei Co., Ltd., MEH-7851SS), 0.35% by mass of silane coupling agent (manufactured by Shin-Etsu Chemical Co., Ltd., KBM-573), 0.26% by mass of curing accelerator (triphenylphosphine, TPP), and 0.27% by mass of ester wax (manufactured by Clariant Chemicals, Lico-WAX E) were mixed and homogenized, and then heated and kneaded with a biaxial roll heated to 80°C, extruded, cooled and solidified, and then pulverized to a predetermined particle size with a pulverizer to obtain a powdered epoxy resin composition (measurement sample) that is solid at room temperature. The spiral flow (cm) was measured when the obtained measurement sample was transfer molded under the following conditions. The results are shown in Table 1. (conditions) Mold size: φ3mm spiral shape Mold temperature: 175℃ Injection pressure: 65kgf / cm 2 ·Molding time: 90 seconds When the obtained spiral flow was 40 cm or more, the fluidity was judged to be excellent, and when it was less than 40 cm, the fluidity was judged to be poor.
[0072] <Narrow gap filling length: Evaluation of filling ability> Using the measurement sample obtained above, the narrow gap filling length (cm) was measured when transfer molding was performed under the following conditions. The results are shown in Table 1. (conditions) Mold size: 5mm x 60mm x 0.03mm (width x length x thickness) Mold temperature: 175℃ Injection pressure: 65kgf / cm 2 ·Molding time: 90 seconds When the narrow gap filling length was 20 cm or more, the narrow gap filling property was judged to be excellent, and when it was less than 20 cm, the narrow gap filling property was judged to be poor.
[0073] The silica powders of Examples 1 to 5 were able to reduce the dielectric tangent when blended with a resin compared to Comparative Examples 2 and 5, and showed superior narrow gap filling properties when blended with a resin compared to Comparative Examples 1 to 4.
Claims
1. The dielectric loss tangent of the resin sheet sample at 40 GHz measured according to the following procedure is 2.0 x 10 -3 A silica powder having the following structure: The amount of moisture generated by the time the temperature reaches 200°C, as measured by the Karl Fischer method, is 500 ppm or less. The specific surface area measured by the BET single point method using nitrogen gas adsorption is 0.2 m 2 / g or more 5.4m 2 / g or less, and The particle diameter at the point where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 90% is defined as D 90 When this is done, D 90 is 3.0 μm or more and 75 μm or less, Silica powder. (procedure) The silica powder is mixed with polyethylene powder so that the filling amount is 40 volume %, and the resin sheet sample is molded using the obtained mixed powder. The dielectric loss tangent at 40 GHz is measured using the obtained resin sheet sample by a resonance method.
2. 2. The silica powder according to claim 1 , A silica powder having a mode diameter of 2.5 μm or more and 40 μm or less in a particle size frequency distribution measured by a wet laser diffraction scattering method.
3. 3. The silica powder according to claim 1 or 2, A silica powder having a maximum peak frequency of 10% or less in a particle size frequency distribution measured by a wet laser diffraction scattering method.
4. 3. The silica powder according to claim 1 or 2, The value of the most frequent diameter in the particle size frequency distribution measured by a wet laser diffraction scattering method is Dm (μm), and the value of the specific surface area is S (m 2 / g), Dm / S is 0.6 or more,
5. 3. The silica powder according to claim 1 or 2, A silica powder in which the frequency of particles having a particle size of 15.7 μm or more is 50% or less in a particle size frequency distribution measured by a wet laser diffraction scattering method.
6. 3. The silica powder according to claim 1 or 2, A silica powder having a particle size frequency distribution measured by a wet laser diffraction scattering method in which the frequency of particles having a particle size of less than 0.5 μm is 15% or less.
7. 3. The silica powder according to claim 1 or 2, The particle diameters at the points where the cumulative volume from the small particle side in the volume frequency particle size distribution measured by the wet laser diffraction scattering method is 10%, 50%, and 100% are defined as D 10 , D 50 , D 90 When this is done, (D 90 -D 10 ) / D 50 The silica powder has a molecular weight of 10 or less.
8. 3. The silica powder according to claim 1 or 2, A silica powder having an average sphericity of 0.85 or more.
9. 3. The silica powder according to claim 1 or 2, Silica powder having an amorphous rate of 95.0% or more.
10. 3. The silica powder according to claim 1 or 2, A silica powder having an elemental uranium and elemental thorium content of 20 ppb or less.